Teacher Work Motivation in the Post-COVID-19 Era: A Descriptive Study at Vocational High Schools in East Padang in Support of SDG 4 (Quality Education) - Syahril Syahril; Ahmad Sabandi; Sulastri Sulastri (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: To analyze the level of teachers' work motivation after the COVID-19 pandemic in vocational high schools in East Padang and to examine its implications for improving educational quality. The findings are expected to provide evidence-based recommendations for strengthening teacher motivation as an essential component in achieving Sustainable Development Goal (SDG) 4: Quality Education. Method: A descriptive quantitative research design. Data were collected using a structured questionnaire distributed to teachers at vocational high schools in East Padang. The collected data were analyzed using descriptive statistical techniques to determine the level of teachers' work motivation based on several motivational indicators. Results: The findings indicate that the overall level of teachers' work motivation reached an achievement score of 78%, which falls within the fairly high category. Responsibility, perseverance, independence, and work enthusiasm contributed positively to teachers' motivation; however, several aspects still require improvement. The study also highlights the important role of school principals in enhancing teachers' motivation through supportive leadership, adequate facilities, and appropriate incentive systems. Strengthening teachers' motivation is expected to improve teaching quality and student learning outcomes, thereby supporting the realization of inclusive and quality education. Novelty: The study provides recent empirical evidence regarding teachers' work motivation in the post-COVID-19 educational context at vocational high schools in Indonesia. Unlike previous studies that primarily examined teacher motivation before or during the pandemic, this research specifically focuses on post-pandemic conditions and emphasizes the importance of school leadership in sustaining teacher motivation. Furthermore, the study links teacher motivation with the achievement of SDG 4, highlighting its contribution to improving educational quality and promoting sustainable educational development.